Nursing Care for Post Partum Mothers with Post Section Caesarean in the Inpatient Room in Kabanjahe Regional Hospital - Henry Anta Lesmana (Jurnal Kesehatan Amanah, 2024)
Abstract. Post partum is time after labor can Also called time postpartum ( puerperium ) that is time after labor Which required For recovery return tool content Which duration 6 week.Sectio Caesarea is an artificial delivery in which the fetus is born through an incision in the front wall of the uterus. stomach And wall uterus with condition uterus in condition intact as well as heavy fetus in on 500 grams HOSPITAL Dr. Achmad Mochtar Bukittinggi in the last 6 months of 2019, the incidence of cesarean section was caesarean section as many as 198 people. The author's purpose in making this report is to be able to understand the concept about Mother post partum with post operation section caesarean And do care nursing on client Mrs. R in the Obstetrics inpatient room of Dr. Achmad Mochtar Hospital Bukittinggi. Post operation section caesarean is incident Which often happen in circles public Indonesia, where postpartum mothers with post-caesarean section operations are not handled properly right will cause bleeding, causing death. Therefore it is suggested to the agency House sick to conduct assessments, planning, action And evaluation in a way appropriate and true.